أشكال الصراع الإجتماعي للشخصية الرئيسي في رواية "اللص والكلاب" على أساس نظرية الاجتماعية الأدبية لألان سوينجوود - Nida, Nushrotun; Yuliani, Annisa; Mardiyanti, Yanti (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
The occurrence of social conflict in literature is a reflection of the state of society. Social conflict among society is normal because each person has different interests or needs. This research aims to find out the forms of social conflict of the main character in the novel “Allishu wa alkilab” by Naguib Mahfouz on the basis of Alan Swingwood’s theory. This research uses a qualitative approach and a method of collecting data using note-taking techniques. The method of data analysis used in this research is descriptive analysis. This research shows that the forms of social conflict for the main character in the novel “Allishu wa alkilab” by Naguib Mahfouz, based on Alan Swingwood’s theory, mean internal conflict (anxiety and anger) and external conflict (murder, threats, betrayal, and hostility). The social conflict that occurs in the main character in the novel is a social reflection of Saeed, as further research can analyze the internal conflict of the main character in this novel from the perspective of literary psychology. إن حدوث الصراع الاجتماعي في الأدبي هو انعكاس لحالة المجتمع. الصراع الاجتماعي بين المجتمع أمر طبيعي لأن كل شخص لديه اهتمامات أو احتياجات مختلفة. يهدف هذا البحث لمعرفة أشكال الصراع الاجتماعي لشخصية الرئيسى فى الرواية "اللص والكلاب" لنجيب محفوظ على أساس نظرية ألان سوينجوود. يستخدم هذا البحث المنهج النوعي، وطريقة جمع البيانات بتقنية تدوين الملاحظات، وأما طريقة تحليل البيانات المستخدم في هذا البحث هو التحليل الوصفي. يبين هذا البحث أن أشكال الصراع اللإجتماعي لشخصية الرئيسى فى الرواية "اللص والكلاب" لنجيب محفوظ على أساس نظرية ألان سوينجوود ينقسان يعني الصراع الداخلي (القلق والغضب) والصراع الخارجي (القتل والتهديد والخيانة والعدواة). و إن الصراع الاجتماعي الذي يحدث في الشخصية الرئيسية في الرواية هو انعكاس اجتماعي لسعيد، حيث يمكن لمزيد من البحث تحليل الصراع الداخلي للشخصية الرئيسية في هذه الرواية من منظور علم النفس الأدبي.